Digital literacy tools and methodologies for information society - Rivoltella, P. C. (Pier Cesare) (IRM Press, 2008)
"This book defines a conceptual framework for understanding social changes produced by digital media and creates a framework within which digital literacy acts as a tool to assist younger generations to interact critically with digital media and their culture, providing scholars, educators, researchers, and practitioners a technological and sociological approach to this cutting-edge topic from an educational perspective"--Provided by publisher.